The Effect of Trust and Service Quality on Loyalty with Satisfaction as a Mediation Variable: A Case Study on Deposit Customers of PT. BPR BKK Jepara (Perseroda) - Basri Basri; Endang Tjahjaningsih (Universitas KH. Abdul Chalim Mojokerto, 2026)
Customers are an essential component as one of the elements of bank credibility. Customer loyalty can be used as an indicator to see the bank's ability to meet customer needs. This study aims to analyze efforts to increase customer loyalty through trust, service quality and satisfaction. The population in this study were deposit customers at PT BPR BKK Jepara (Perseroda). The sample in this study was 100 respondents. Sampling was taken using a purposive sampling technique with the following criteria: being a customer of the operational head office, aged over 17 years and being a customer for more than 1 year. Data analysis techniques used include: respondent description, variable description, instrument test and regression analysis test, and mediation test using the Sobel test. The results of the data analysis indicate that customer trust does not affect satisfaction, service quality has a significant positive effect on satisfaction, customer trust has a significant positive effect on loyalty, service quality has a significant positive effect on loyalty, satisfaction has a significant positive effect on loyalty. The results of the mediation test indicate that satisfaction does not mediate the effect of trust on loyalty. However, satisfaction mediates the effect of service quality on loyalty.